Vapor-phase-synthesized fluoroacrylate polymer thin films: thermal stability and structural properties - Christian, Paul; Coclite, Anna Maria (Beilstein Journal of Nanotechnology, 2017)
In this study, the thermal, chemical and structural stability of 1H,1H,2H,2H-perfluorodecyl acrylate polymers (p-PFDA) synthetized by initiated chemical vapor deposition (iCVD) were investigated. PFDA polymers are known for their interesting crystalline aggregation into a lamellar structure that induces super-hydrophobicity and oleophobicity. Nevertheless, when considering applications which involve chemical, mechanical and thermal stresses, it is important to know the limits under which the crystalline aggregation and the resulting polymer properties are stable. For this, chemical, morphological and structural properties upon multiple heating/cooling cycles were investigated both for linear PFDA polymers and for differently strong cross-linked alterations thereof. Heat treatment leaves the chemical composition of the linear PFDA polymers largely unchanged, while a more ordered crystalline structure with smoother morphology is observed. At the same time, the hydrophobicity and the integrity of the polymer deteriorate upon heating. The integrity and hydrophobicity of cross-linked p-PFDA films was preserved likely because of the lack of internal strain due to the coexistence of both crystalline and amorphous phases. The possibility to finely tune the degree of cross-linking can therefore expand the application portfolio in which PFDA polymers can be utilized.
Keywords: EGDMA; iCVD; in situ; PFDA; spectroscopic ellipsometry; temperature dependent; X-ray diffraction